Crusty Leaf Spot Disease of Mango - Lim, Tong Kwee; Khoo, Khay Chong (1983)
A crusty spot disease on mango leaves was found to be ubiquitous on neglected mango trees throughout Peninsular Malaysia. Light and scanning electron microscope studies revealed the crusty structures to be the ascostromata of the fungus, Zimmennaniella trispora. This disease can cause severe leaf spotting of trees. This is the first report of z. trispora as a leaf parasite of mango in Malaysia.